Peran Literasi Digital dalam Penguatan Profil Pelajar Pancasila Dimensi Mandiri, Bernalar Kritis, dan Kreatif - I Wayan Dede Putra Wiguna; Ni Wayan Sudarti, S.Pd., M.Hum. (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
Digital literacy is becoming increasingly important in today's education, especially in developing student profiles that are independent, critical reasoning, and creative in the context of Pancasila. This study aims to describe the role of digital literacy in strengthening the profile of Pancasila students in these three dimensions. This research uses literature method to collect information from various related sources. The results showed that digital literacy has a significant role in strengthening and developing the profile of students who are independent, critical reasoning, and creative in the context of Pancasila. Digital literacy enables learners to access, evaluate, create, use information wisely, and communicate effectively through a variety of digital media. Thus, the integration of digital literacy in education can help strengthen the profile of Pancasila students in the independent, critical, and creative dimensions.